(untitled) (Eurasian Research Bulletin, 2024)
This paper explores the pedagogical approaches and strategies for fostering moral and aesthetic competence in students. Drawing on theoretical frameworks and practical considerations, the paper examines the significance of integrating moral and aesthetic education into the curriculum. It discusses instructional strategies such as literaturebased discussions, inquiry-based learning, and experiential learning opportunities, as well as practical approaches including interdisciplinary integration and reflective practices.